Efficacy of standard chemotherapy regimens in children and adolescents suffering from respiratory tuberculosis - E. F. Luginova; O. I. Gurieva; D. А. Nikolaeva (Туберкулез и болезни лёгких)
The objective of the study: to assess the efficacy of standard chemotherapy regimens in the treatment of children and adolescents suffering from respiratory tuberculosis.Subjects and methods. 272 children aged 0 to 17 years old with newly diagnosed respiratory tuberculosis were on treatment.Results. Treatment of children suffering from respiratory tuberculosis with standard chemotherapy regimens made it possible to achieve cure of tuberculosis in 264/272 (97.1%) children and adolescents aged 0-17 years old, 8/272 (2.9%) underwent surgery additionally to chemotherapy.